Crowdworking: Neue Herausforderungen für das Arbeitsrecht in Deutschland - Michele Dilenge (IUBH Internationale Hochschule, 2020)
Crowdworking is a new organizational form of work that is attractive for both employees and companies. A great advantage is the flexibility of the design and the need-based access to certain services. Work processes can be made more efficient and flexible. Crowdworking has not yet become an integral part of the labor market. The volume of work performed by crowdworking cannot yet be adequately determined. However, it can be assumed that the Covid 19 pandemic threatens an economic slump that will lead to a reorganization of the work organization. Many employees already "practice" this decentralized form of work in their home office. Employees will be organized in various forms. Employees affected by layoffs will increasingly seek a new form of employment through crowdworking and will be forced to become self-employed in this way. Companies will reorganize the work for both the permanent internal employees and delegate many services - depending on requirements - to external crowdworkers via platforms. It is to be expected that the Federal Labor Court will deal with the legal framework of crowdworking in 2020 and will very likely set new guidelines, not least due to the revision approved by the State Labor Court in Munich. Crowdworking is becoming increasingly important in the world of work, which is why there is a great need for clarification for everyone involved. The principle of freedom of contract applies in Germany, but de facto the negotiating power and freedom of design of the crowd worker compared to the mediating platforms is very limited. In the meantime, clients and platform operators are well advised to limit possible risks when employing crowd workers by carefully drafting contracts. Minimum remuneration standards would be a first sensible step. With the new EU Directive 2017/0355 (COD), legislators are required to set up clear and unambiguous "guard rails" for crowdworking. The constantly changing world of work currently demands a high degree of flexibility - both from companies and from employees. Therefore, the legislator should define the term crowd worker in the labor law sense, not least to maintain social peace in the world of work and in society.
Keywords: 650; Arbeitszeit; Arbeitslohn; Crowdworking; Plattformökonomie; Scheinselbständigkeit